Pan-africanismo, historiografia e educação: experiências em Cabo Verde e no Brasil - Gomes, Fábio Florenço (2014)
This research intends to confront the theoretical and the conceptual proposals of the textbook General History of Africa, published by UNESCO, as well as the locations of the ancient Classic African civilizations in the syllabi of the textbooks adopted in History classes of mediumschools in Brazil and secondary schools in Cape Verde. The general objective is to investigate the relationship between the methodology and African antiquity in the textbooks General History of Africa I and II, published by UNESCO It also analyses what is taught about Africa in Ancient Human History. The specific objectives are 1) to build a historical and social approach to teach about África General History based on Pan-Africanism and Historical Knowledge; 2) to identify the location of Ancient Africa in History in the curriculums and textbooks adopted in public schools in Fortaleza (Brazil) and in Santiago Island (Cape Verde); The theoretical background of this research is based on authors such as ZERBO (1972-2010), DIOP (1954-2010), RODNEY (1975-1980), CABRAL (1978), CUNHA (2006), MONIZ (2009), ASANTE (1989), ANJOS (2002), NASCIMENTO (2001), UNESCO (2009-2011), among other scholars devoted to the study of Ancient Africa and its methodology, social movements, Pan-Africanism, Ancient Africa and Education. The methodology adopted is a case study conducted through quantitative analysis of textbooks and syllabi, as well as interviews with teachers. The instruments employed for data collection are a bibliographical research, analysis of documents, and semi-structured interviews with teachers. In order to record the research data, a field journal and audio recordings have been used. After that, preliminary conclusions of the research are presented, even though the findings during the field work are still being systematized. However, by then it is already possible to affirm that the geographical locations, the settlements, and the legacy of the ancient classic African civilizations are dealt with under the same Eurocentric principles present in other textbooks and syllabi adopted in fundamental schools in Brazil and in secondary schools in Cape Verde. The political and ideological apology of the mixture of races exerts influence in the formation of identity, educational background and professional attitude of History teachers in Brazil and in Cape Verde. There is also a shortage of materials in the libraries of the institutions visited. Moreover, the textbooks General History of Africa I and II and The Pedagogical Use of General History of África (both published by UNESCO) are neither well-known nor widely adopted in Cape Verde or in Brazil. These factors point at 1) the lack of knowledge and interest, as well as at the conflict of students with African History, its culture and identity; 2) the need to teach and to write textbooks which are minimally based on the awareness, on the heritage and on the African regional integration.